2005
DOI: 10.1097/01.sla.0000161982.57360.1b
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Biliary Cystadenoma

Abstract: Biliary cystadenoma must be recognized and treated differently than most hepatic cysts. There remains a need for education about the imaging findings for biliary cystadenoma to reduce the demonstrated delay in appropriate treatment. Traditional treatment of simple cysts such as aspiration, drainage, and marsupialization results in near universal recurrence and occasional malignant degeneration. This experience demonstrates effective options include total ablation by standard hepatic resection and cyst enucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
153
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(169 citation statements)
references
References 17 publications
(11 reference statements)
4
153
0
7
Order By: Relevance
“…However, core biopsy is unlikely to yield sufficient tissue in case of simple cyst or cystadenoma; it also is not suitable for the diagnostics of focal malignancy and rarely can lead to peritoneal carcinomatosis [13]. Therefore radiological diagnostics, especially computed tomography, is essential [117]. Grossly, biliary cystadenocarcinoma is multicystic.…”
Section: Cystic Biliary Tumoursmentioning
confidence: 99%
See 2 more Smart Citations
“…However, core biopsy is unlikely to yield sufficient tissue in case of simple cyst or cystadenoma; it also is not suitable for the diagnostics of focal malignancy and rarely can lead to peritoneal carcinomatosis [13]. Therefore radiological diagnostics, especially computed tomography, is essential [117]. Grossly, biliary cystadenocarcinoma is multicystic.…”
Section: Cystic Biliary Tumoursmentioning
confidence: 99%
“…Vascularity of septa is characteristic for cystic biliary tumours [14] and is considered by some specialists to be more reliable in distinguishing biliary cystadenoma from cyst than the simple presence of septations [117]. Biliary cystadenoma is characterised by smooth and thin internal septa, but presence of enhanced mural nodules in the outer wall or septa is the most important sign of malignancy.…”
Section: Cystic Biliary Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen sections are used to direct the surgical treatment but they can miss the diagnosis of hepatobiliary cystadenoma during a fenestration as was the case in our patient [7] . Thomas et al [8] reported that tumor recurrence occurs in two thirds of the patients, who have only local or pericystic excision. In contrast, only 10% of the patients, who have hepatic lobectomy, hemihepatectomy or radical excision of cystadenoma with a rim of normal tissue with a diameter of 2 cm, require further surgery for recurrence.…”
Section: To the Editormentioning
confidence: 99%
“…In contrast, only 10% of the patients, who have hepatic lobectomy, hemihepatectomy or radical excision of cystadenoma with a rim of normal tissue with a diameter of 2 cm, require further surgery for recurrence. Therefore, the detection of hepatobiliary cystadenoma after a laparoscopic surgical approach implies many challenging therapeutic dilemmas [8,9] .…”
Section: To the Editormentioning
confidence: 99%